Hannah Arendt on the "stateless"-condition - Mancheno, Tania (HannahArendt.net, 2016)
In this paper, I intend to revisit Hannah Arendt’s analysis on statelessness in order to discuss the latest development of continental Europe’s political geography. The reconstruction of her approach to "statelessness" should guide a reflection on the contemporary relationship among national territory, rights and illegality. This analysis shall be based around two Arendtian terms: nomos and natality. I shall address the following questions: how does Arendt address statelessness? How is the relationship between human rights and the banishment of people outside the space of the nation-state being justified? Under which criteria is the territorial enclosure being legitimized? Could the Arendtian category of "stateless" be interpreted as a political, an apolitical, or rather a depoliticized human condition?